The role of non-financial aspects in project appraisal –the practice of portuguese firms - Moutinho, Nuno (2010)
Project appraisal has traditionally put its emphasis on the financial aspects of projects,mainly the quantitative ones, underestimating other areas of analyses where factors of a qualitative nature, intangible and subjective, may also affect the implementation and value of projects. Non financial evaluation supply information about less tangible factors and is expected to identify competitive advantages and risks that financial techniques cannot capture. In general there are few empirical studies addressing these other aspects. Most surveys are addressed to the financial techniques. With our work we aimed to identify the importance of non financial aspects at the decision making process and the evaluation of projects, in practice, in particular to investigate the practices of Portuguese companies in this field, that is: investigate to what extent are non financial aspects taken into account in investment decisions; which non financial aspects are most relevant; which procedures are adopted to minimize the non financial risks; and which evaluation methods are used to incorporate non financial elements at the decision-making process. The results of our study support the importance of incorporating non financial aspects into the appraisal of projects, and show how some of those aspects have greater relevance than that attributed to the financial elements. The study also points to the strategic and technical aspects of projects as the most relevant non financial factors considered by Portuguese firms. The financial analysis, according to the empirical data collected, comes only in third place of importance, both at the appraisal and at the decision-making stages. Commercial factors, showed similar relevance to the financial ones. This work also allows us to differentiate the importance of the different areas of analysis, and the way this analysis is done, according to the characteristics of the company and the project, the company’s administration and the project manager. In this way, we find that, type of industry, size and debt of the company, type, duration, size and risk of the project, the academic background of the chairman of the board, and of the project manager, and also the tenure of the board’s chairman, are among the factors that have the most influence in the importance attributed by firms to the different areas of project appraisal.